Apparatus Quality as the Main Determinant of Financial Report Quality: Kualitas Aparatur sebagai Penentu Utama Kualitas Laporan Keuangan - Sri Wulandari; Sugianto Sugianto; Yenni Samri Juliati (Academia Open, 2025)
Background: The quality of financial reporting within local governments plays a critical role in ensuring transparency and accountability. Specific Background: Despite regulations mandating the application of government accounting standards and internal control mechanisms, empirical inconsistencies remain regarding their actual influence on financial reporting quality. Knowledge Gap: There is limited empirical evidence on how internal control, accounting standard implementation, and apparatus quality affect financial reporting in regional government settings, particularly in under-examined areas such as Sei Balai. Aim: This study investigates the impact of government accounting standards implementation, internal control, and apparatus quality on the financial reports of the Sei Balai District Office. Results: Findings reveal that only the quality of government apparatus exerts a significant and positive influence on financial reporting, while accounting standards and internal control do not demonstrate statistically significant effects. Novelty: This research contributes a localized case-based empirical insight into factors influencing financial report quality in regional governments, diverging from generalized assumptions that all regulatory compliance measures inherently yield better reporting outcomes. Implications: These results suggest that capacity-building for human resources may be more crucial than procedural compliance in improving the quality of financial reports, informing policymakers in resource prioritization. Highlights: Highlights the dominant role of apparatus quality in financial reporting. Reveals limited impact of accounting standards and internal control. Offers empirical insights from a localized regional government context. Keywords: Government Accounting Standards, Internal Control, Apparatus Quality, Financial Reporting, Local Government